Micron-scale laser-wire scanner for the KEK Accelerator Test Facility extraction line - Boogert, S; Blair, G; Boorman, G; Bosco, A; Deacon, L; Karataev, P; Aryshev, A; Fukuda, M; Terunuma, N; Urakawa, J; Corner, L; Delerue, N; et al. (2010)
A laser-wire transverse electron beam size measurement system has been constructed and operated at the Accelerator Test Facility (ATF) extraction line at KEK. The construction of the system is described in detail along with the environment of the ATF related to the laser wire. A special set of electron beam optics was developed to generate an approximately 1μm vertical focus at the laser-wire location. The results of our operation at the ATF extraction line are presented, where a minimum rms electron beam size of 4.8±0.3μm was measured, and smaller electron beam sizes can be measured by developing the method further. The beam size at the laser-wire location was changed using quadrupoles and the resulting electron beam size measured, and vertical emittance extracted.© 2010 The American Physical Society.